Crescimento micelial, produção e características bromatológicas do shiitake em função de linhagens e de propriedades físicas e químicas de espécies e clones de eucalipto - Andrade, Meire Cristina Nogueira de [UNESP] (2007)
Mycelium growth, production and bromatologicals characteristics of shiitake in function of lineages and chemical and physical properties of eucalyptus clones and species were evaluated. In Experiment 1, mycelium growth of two Lentinula edodes (Berk.) Pegler (LE-95/01 and LE-96/18) species in culture mediums prepared with sawdust extract from seven species (E. saligna, E. grandis, E. urophylla, E. camaldulensis, E. citriodora, E. paniculata e E. pellita) and three eucalyptus clones (hybrid E. grandis x E. urophylla) was analyzed. The experimental design was totally randomized, in 2x10 factorial design, totalizing 20 treatments with 10 repetitions, being that each repetition corresponded to one Petri dish. In Experiment 2, mycelium growth of eight L. edodes lineages (LE-96/17, LE-95/02, LE-95/07, LE-98/55, LE-96/18, LE-95/01, LE-96/13 and LE-98/47) in culture mediums prepared with sawdust extract from Eucalyptus spp was evaluated. The experimental design was totally randomized, with 8 treatments and 8 repetitions, being that each repetition corresponded to one Petri dish. In Experiment 3, production and bromatological characterization of two Lentinula edodes lineages cultivated in seven species and three clones of eucalyptus was evaluated. The experimental design was totally randomized, in 2x10 factorial design, totalizing 20 treatments with 40 repetitions, being that each repetition corresponded to one log. In Experiment 4, physical and chemical properties of seven species and three clones of eucalyptus before and after the cultivation of two L. edodes lineages was evaluated. The experimental design was totally randomized, in 2x10 factorial design, totalizing 20 treatments with 9 repetitions, being that each repetition corresponded to one log. The culture medium that provided highest averages of mycelium growth of L. edodes lineages LE-95/01 and LE-96/18 was the one with... (Complete abstract click electronic access below)